THE INFLUENCE OF WORK CULTURE AND COMMUNICATION ABILITY TO THE PERFORMANCE OF SHIPS CREW IN SURABAYA NORTH QUAY - Nyoman Ardiana Listriyawati (Indonesian Naval Technology College STTAL, 2021)
In the work environment on the ship, the crew is expected to have a work culture and the ability to communicate using good English to achieve good performance on the ship. The purpose of this study was to determine how positively and significantly the influence of work culture and the ability to communicate using English to the performance of the crew. The method used by distributing questionnaires to respondents, namely crew members with quantitative analysis methods, namely multiple linear regression analysis, t test, F test and determination test so that it can be seen the effect of work culture and the ability to communicate on the performance of the crew. The results obtained in this study, there is a positive influence between work culture and communication skills on the performance of the crew. In the end, it is hoped that this research will give a reference for shipping companies, ship crews and related parties. Keywords: Work Culture, Communication Ability, Crew Performance.